2011
DOI: 10.1063/1.3596949
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid density functional theory description of N- and C-doping of NiO

Abstract: The large intrinsic bandgap of NiO hinders its potential application as a photocatalyst under visible-light irradiation. In this study, we have performed first-principles screened exchange hybrid density functional theory with the HSE06 functional calculations of N- and C-doped NiO to investigate the effect of doping on the electronic structure of NiO. C-doping at an oxygen site induces gap states due to the dopant, the positions of which suggest that the top of the valence band is made up primarily of C 2p-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 50 publications
3
16
1
Order By: Relevance
“…The exact exchange contribution of 25% was used and this produced a band gap of 3.20 eV for anatase-TiO 2 , in essentially exact quantitative agreement with the experimental value [21], and far superior to previous conventional DFT modelling of titania by both ourselves [7,8] and others [2,6,9,11,12]; this exact exchange contribution of 25% was also suggested originally by Becke by fits of atomization energy data of molecules and is reasonably applicable to a wide extent of materials in hybrid-DFT [22]. It should be noted that the use of the hybrid HSE06 functional has led to improved results in recent studies of the electronic properties of a wide variety of materials vis-à-vis previous nonhybrid DFT and DFT + U studies, such as the technologically important SiC [23], NiO [24] and, importantly for this study, titania [10,14,[25][26][27]; therefore, this serves as a useful motivation for the use of HSE06 in this study. In addition, Deák et al [28] concluded that the HSE06 functional offers improved accuracy for the energetics of defect levels and associated charge transition levels in a variety of materials, as well as describing group-IV semiconductors well.…”
Section: Methodsmentioning
confidence: 69%
“…The exact exchange contribution of 25% was used and this produced a band gap of 3.20 eV for anatase-TiO 2 , in essentially exact quantitative agreement with the experimental value [21], and far superior to previous conventional DFT modelling of titania by both ourselves [7,8] and others [2,6,9,11,12]; this exact exchange contribution of 25% was also suggested originally by Becke by fits of atomization energy data of molecules and is reasonably applicable to a wide extent of materials in hybrid-DFT [22]. It should be noted that the use of the hybrid HSE06 functional has led to improved results in recent studies of the electronic properties of a wide variety of materials vis-à-vis previous nonhybrid DFT and DFT + U studies, such as the technologically important SiC [23], NiO [24] and, importantly for this study, titania [10,14,[25][26][27]; therefore, this serves as a useful motivation for the use of HSE06 in this study. In addition, Deák et al [28] concluded that the HSE06 functional offers improved accuracy for the energetics of defect levels and associated charge transition levels in a variety of materials, as well as describing group-IV semiconductors well.…”
Section: Methodsmentioning
confidence: 69%
“…The calculations are conducted using the generalized gradient approximation (GGA) of the Perdew–Burke–Ernzerh (PBE) exchange-correlation functional, which is modified by the unrestricted Hubbard- U correction for the strong on-site Coulomb interaction. , The modifiers (i.e., U and J ) applied on Ni are U = 6.3 eV and J = 1.0 eV . On the basis of the experimental outcomes, the chosen terms for the Hubbard- U correction have captured the behavior of the studied system. Moreover, the computational prediction of the lattice constants of NiO ( a = b = c = 4.161 Å and α = β = γ = 90°) obtained from this study is consistent with experimental observations ( a = b = c = 4.15 Å and α = β = γ = 90°) . The projector-augmented wave (PAW) , method is chosen to treat the core–valence electron interactions.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[20][21][22][23] Generally, replacing O atoms with other non-metal elements will influence the electronic structures of semiconductors. [49][50][51][52] As shown in Fig. 4(a) and (b), C-doping introduces three band gap states of C 2p orbital character in the spin-up and spindown bands.…”
Section: Doping On the Sro-terminated Srtio 3 (001) Surfacementioning
confidence: 99%